MENINGKATKAN KREATIVITAS ANAK MELALUI PERMAINAN BALOK DI PAUD ISLAM HAWARI TANJUNG GANTI I - Dahniar Dahniar; Elise Muryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve early childhood creativity through block play activities at PAUD Islam Hawari Tanjung Ganti I. The research was motivated by initial observations indicating that children’s creativity levels were relatively low, with approximately 60% of children showing limited active engagement in block play activities. The observed issues included low ability to express ideas, limited variation in creations, and a tendency to imitate peers’ work. This study employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages conducted in two cycles. The participants consisted of 15 early childhood learners. Data were collected through observation and documentation based on creativity indicators, namely fluency, flexibility, originality, and elaboration. The data were analyzed using descriptive quantitative techniques. The findings revealed a significant improvement in children’s creativity from Cycle I to Cycle II. In Cycle I, the average creativity score was 2.35, categorized as “Beginning to Develop,” while in Cycle II it increased to 3.45, categorized as “Very Well Developed.” The improvement was observed across all creativity indicators, with an overall increase of 1.1 points. These results indicate that block play activities are effective in enhancing children’s creativity by providing opportunities for exploration, experimentation, idea generation, and imaginative construction. The study suggests that block play can be used as an alternative learning medium to stimulate creativity in early childhood education settings.